Knowledge transfer between small manufacturing enterprises - Skandalakis, Alexandros (Cranfield University, 1999)
This thesis illustrates that didactic and gnostic practices, identified through a structured Knowledge Transfer Framework, can effect business improvement in Small and Medium-sized Enterprises. Small and Medium-sized Enterprises form a significant heterogeneous economic force. They strengthen the capacity of a country to generate employment and wealth for the general benefit of regional and national economies. The importance of SMEs in the prosperity of a society and their contribution to new job creation, coupled with the recognition that they seem to underperform, enhances the need to assist smaller companies improve their performance. The author investigated the essence of Small and Medium Enterprises, conducted a literature review in Benchmarking and Self-Assessment principles and asserted the importance of knowledge in sustainable business development. The author introduced the SME Knowledge Deficit, assessed its implications on business improvement, and elaborated that the Knowledge Deficit can be addressed through the establishment of a Knowledge Transfer Framework in the SME domain. The thesis establishes the characteristics of a Knowledge Transfer Process for SMEs, leading to the development of a Knowledge Transfer Framework in the domain. This supports business improvement. The framework provides diagnostic assessment of business performance, task defined specific solutions embracing better practices and innovative advances through Win-Win Benchmarking. The analysis connects to business performance, and recalibrates Small and Medium-sized Enterprises towards better practices. Improved business performance is based on knowledge sourced from superior performing companies. This is shown to be effective despite the polyonymous and indiomorphous nature of their business environment. The Knowledge Transfer Framework combines Self-Assessment and Benchmarking practices. It is implemented through Focus Group practices. This practical research was validated in a specially selected portfolio of Small and Medium-sized Enterprises in the United Kingdom. It draws upon practical application in Spain and Germany. The author demonstrated that Knowledge Transfer can successfully occur amongst Small and Medium-sized Enterprises if approached through a structured methodology. The foundation of a grand Benchmarking database is not essential for Knowledge Transfer. Superior practices can be successfully sourced and disseminated via a structured Knowledge Transfer Framework and a portfolio of specially selected enterprises displaying superiority in a designated area of their business, rather than from global best practices.